Teachers’ Experiences with Flipped Classrooms in Senior Secondary Mathematics Instruction - Adebayo Akinyinka Omoniyi; Loyiso Currell Jita; Thuthukile Jita (Computers)
The quest for effective pedagogical practices in mathematics education has increasingly highlighted the flipped classroom model. This model has been shown to be particularly successful in higher education settings within developed countries, where resources and technological infrastructure are readily available. However, its implementation in secondary education, especially in developing nations, has been a critical area of investigation. Building on our earlier research, which found that students rated the flipped classroom model positively, this mixed-method study explores teachers’ experiences with implementing the model for mathematics instruction at the senior secondary level. Since teachers play a pivotal role as facilitators of this pedagogical approach, their understanding and perceptions of it can significantly impact its effectiveness. To gather insights into teachers’ experiences, this study employs both close-ended questionnaires and semi-structured interviews. A quantitative analysis of participants’ responses to the questionnaires, including mean scores, standard deviations and Kruskal–Wallis H tests, reveals that teachers generally record positive experiences teaching senior secondary mathematics through flipped classrooms, although there are notable differences in their experiences. A thematic analysis of qualitative interview responses highlights the specific support systems essential for teachers’ successful adoption of the flipped classroom model in senior secondary mathematics instruction.